Linear assembly of hexadecanethiol coated gold nanoparticles - Sidhaye, Deepti S.; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2008)
An interesting formation of linear assembly of hexadecanethiol coated gold nanoparticles is demonstrated. The nanoparticles used were synthesized in an organic medium and then were subjected to digestive ripening to finally yield monodisperse nanoparticles. A simple drop casting on TEM grid lead to the results observed. Based on the thermo gravimetric analysis, it is hypothesized that inclusion of the particles in Au(I)-thiolate template is mainly responsible for the formation of linear assembly. (c) 2008 Elsevier B.V. All rights reserved.